Harmony with Nature: A Cultural Ecological Study of Mandailing Ethnic Philosophy on the Environment - Ahmad Muhajir (Andalas International Journal of Socio-Humanities, 2023)
This article aims to explore the profound philosophy of life held by the Mandailing ethnic group in maintaining the relationship between humans and the environment from a cultural ecological perspective. Employing an ethnohistorical approach, this research analyzes and synthesizes relevant ethnographic literature along with field research data. The focus of this study is on the philosophies "Poda Na Lima" and "Holong do Maroban Domu, Domu Maroban Parsaulian" as locally inherited wisdom passed down through generations by the Mandailing ethnic group to foster a harmonious relationship with nature. Key figures such as village chiefs, traditional leaders, religious figures, and community elders from Mandailing Natal Regency serve as research subjects and informants. The research findings conclude that "Poda Na Lima" and "Holong do Maroban Domu, Domu Maroban Parsaulian" impart local wisdom values such as compassion, cleanliness, and health in maintaining the harmonization of the relationship between humans and nature. These philosophies continue to be inherited and practiced in the daily lives of the Mandailing community, particularly among agrarian populations in rural areas. In practice, nature is positioned as a source of wisdom, not an object of exploitation, and is internalized to preserve ecological balance.